2011
DOI: 10.4103/0975-3583.78602
|View full text |Cite
|
Sign up to set email alerts
|

A case of arrythmogenic right ventricular cardiomyopathy in a middle-aged woman

Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a kind of heart muscle disease characterized by the gradual replacement of the right ventricular myocardium with fibrous tissue and fat. It could be the major cause of sudden cardiac death with ventricular tachycardia, and there is a variation in the history of the disease. We reported an unusual case of ARVC in a middle-aged woman with congestive heart failure as her first presentation for a long time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Similar to the patient in case 1, this patient had a depressed LVEF, although no preoperative hemodynamic data were available to help quantify the severity of LV failure or presence of pulmonary hypertension. 10 Therefore, it is possible that this patient may have had significant pressure overload contribution to RV failure and TR, and thus, TV repair could have increased RV load and worsened RV failure. In the case described by Gwizdala et al, 11 a patient underwent TV repair for what was thought to be primary TR, similar to case 3.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to the patient in case 1, this patient had a depressed LVEF, although no preoperative hemodynamic data were available to help quantify the severity of LV failure or presence of pulmonary hypertension. 10 Therefore, it is possible that this patient may have had significant pressure overload contribution to RV failure and TR, and thus, TV repair could have increased RV load and worsened RV failure. In the case described by Gwizdala et al, 11 a patient underwent TV repair for what was thought to be primary TR, similar to case 3.…”
Section: Discussionmentioning
confidence: 97%
“…There are 5 isolated reports of surgical correction of TR in ARVD/C in the literature. 10 , 11 , 12 , 13 , 14 Jiang et al 10 reported a case of a patient with long-standing heart failure who underwent TV repair in the setting of progressive and refractory symptoms. This patient experienced an early postoperative death due to low cardiac output.…”
Section: Discussionmentioning
confidence: 99%